Berberine reduces endothelial injury and arterial stiffness in spontaneously hypertensive rats. (2nd April 2020) - Zhang, Gaoxing; Lin, Xiufang; Shao, Yijia; Su, Chen; Tao, Jun; Liu, Xing
ABSTRACT: Background : Changes in circulating endothelial microparticles (EMPs) and endothelial progenitor cells (EPCs) are considered as a new perspective reflection of the endothelial injury and repair status. Our previous studies have demonstrated that berberine improved endothelial function and arterial stiffness in healthy subjects. In this study, we further investigated the effects of berberine on regulating the circulating EMPs and EPCs, and preventing endothelial dysfunction and arterial stiffness in spontaneously hypertensive rats (SHRs). Methods : Twenty male SHRs were randomly divided into two groups: Berberine-treated SHR group and vehicle-treated SHR group. The SHR rats were intragastrically treated with physiologic saline, berberine 50 mg/kg.d or vehicle for 4 weeks, respectively. Ten male Wistar-Kyoto (WKY) rats treated with vehicle served as normotensive controls. Tail systolic blood pressure was monitored every 2 weeks. At the end of the study, aortic pulse wave velocity (aPWV) was measured in vivo, and aorta were collected for measurement of endothelium-dependent vasodilation and immunohistological staining of elastic fiber. Peripheral blood was collected for circulating EMP detection and EPC culture. Results : Compared to normotensive rats, hypertensive rats displayed significantly higher circulating CD31+/CD42− MPs, lower number and colony-forming units (CFUs) of EPCs, worse endothelium-dependent vasodilation, and faster aPWV. Berberine treatment in SHRs partly reduced the blood pressure and circulating EMPs, and augmented EPC numbers and CFUs. In addition, berberine preserved arterial elasticity by lowering aPWV and increasing the content of arterial media elastin fiber, and improved endothelial function by maintaining better endothelium-dependent vasodilation. Robust relationship was observed among circulating CD31+/CD42− MPs, EPC numbers and aPWV. Conclusions : Abnormal changes of circulating EMPs and EPCs in SHRs are associated with endothelial dysfunction and arterial stiffness. Berberine may be a novel therapeutic option for the hypertension-related vascular injury in SHRs.